Super-hydrophilic anti-reflection wear-resistant self-cleaning coating for normal-temperature curing of photovoltaic glass

By applying ultra-hydrophilic transmissive coatings prepared by materials such as nanosilica sol and nanotitanium dioxide on photovoltaic glass, the problem of photovoltaic glass surface pollution reduces light transmittance, and efficient self-cleaning and photoelectric conversion efficiency are achieved.

CN119529570APending Publication Date: 2025-02-28GUANGZHOU SANFU NEW MATERIALS TECH

Patent Information

Application Number
CN202411790508.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The accumulation of pollutants such as dust and dirt on the surface of photovoltaic glass will reduce light transmission and reduce photoelectric conversion efficiency. The existing cleaning methods are costly or inefficient, making it difficult to meet the demand for the growth of the photovoltaic industry.

Method used

Nanosilica sol is used as the main film forming agent, combined with nanotitanium dioxide, silane coupling agent, surfactant and other raw materials, and by combining silica sols with different particle sizes, a super hydrophilic, permeable wear-resistant self-cleaning coating is prepared, which is suitable for the room temperature curing of photovoltaic glass.

Benefits of technology

This coating has the advantages of super hydrophilicity, excellent permeability, weather resistance, wear resistance, antistatic properties and easy cleaning, which significantly improves the self-cleaning effect and photoelectric conversion efficiency of photovoltaic glass, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529570A_ABST
    Figure CN119529570A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of photovoltaic glass coatings, and particularly relates to a super-hydrophilic anti-reflection wear-resistant self-cleaning coating for room-temperature curing of photovoltaic glass, which takes nano silicon dioxide sol as a main film-forming agent to cure and form a film and comprises the following raw materials in parts by weight: 55-90 parts of deionized water, 9-20 parts of nano silicon dioxide sol, 1-10 parts of a silane coupling agent and 0.001-1 part of nano titanium dioxide. The coating is prepared from the following components in parts by weight: 0.01-1 part of a surfactant, 0.01-1 part of modified polyvinyl alcohol, 0.01-1 part of water-based acrylic resin, 0.001-1 part of an antistatic agent, 1-5 parts of a curing agent, 1-5 parts of a flatting agent and 0.1-1 part of a wear-resistant agent. The super-hydrophilic anti-reflection wear-resistant self-cleaning coating has super hydrophilicity, the water contact angle is below 10 degrees, the hydrophilicity, the antistatic property, the anti-reflection property, the wear resistance and other properties of glass can be remarkably improved, and when the super-hydrophilic anti-reflection wear-resistant self-cleaning coating is applied to photovoltaic module glass, the photoelectric conversion efficiency in photovoltaic power generation can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photovoltaic glass coatings, and in particular relates to a super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass that is cured at room temperature. Background Art

[0002] With the increasing demand in the emerging and traditional photovoltaic markets, the global photovoltaic power generation capacity continues to expand, and the global solar photovoltaic power generation market is showing a rapid development trend. The industry benefits have become one of the most concerned issues in the photovoltaic industry. The key to the growth of the photovoltaic industry benefits lies in reducing costs and increasing efficiency, and the key to increasing efficiency lies in improving power generation efficiency and the service life of photovoltaic power station equipment.

[0003] In photovoltaic power generation systems, the main function of solar panels is to convert solar energy into electrical energy. The cleanliness of the photovoltaic glass surface is an important factor affecting power generation efficiency. In natural environments, the accumulation of dust, dirt and other pollutants will reduce the light transmittance of photovoltaic glass, reduce the amount of light reaching the solar panels, and thus reduce the photoelectric conversion efficiency. Dust blocking the surface of photovoltaic glass will also cause the local temperature of the panels to rise, forming hot spots and causing damage. Conventional methods for cleaning photovoltaic panels include natural cleaning, manual cleaning and mechanical cleaning, which are often limited by natural conditions and cleaning costs. Therefore, it is crucial to produce a coating on the surface of photovoltaic glass that has easy-to-clean or even self-cleaning functions and an anti-reflection effect in order to meet the efficiency growth needs of the photovoltaic industry. Summary of the invention

[0004] In response to the demand for efficiency growth in the photovoltaic industry, the present invention provides a super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass that is cured at room temperature. The coating is a non-solvent anti-reflective film, is environmentally friendly, has super-hydrophilicity, and has a water contact angle of less than 10°. It also has the advantages of excellent anti-reflectivity, weather resistance, wear resistance, antistatic properties and easy cleaning, and is suitable for photovoltaic power generation component glass.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] A super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass cured at room temperature, wherein the coating is cured and formed using nano-silica sol as a main film-forming agent; the nano-silica sol comprises a plurality of small-particle silica sol, medium-particle silica sol and large-particle silica sol; the silica particle size of the small-particle silica sol comprises 15 to 20 nanometers, the silica particle size of the medium-particle silica sol comprises 30 to 40 nanometers, and the silica particle size of the large-particle silica sol comprises 50 to 60 nanometers.

[0007] Furthermore, the raw materials include a self-cleaning agent; the nano silica sol is a mixture of large-particle silica sol, small-particle silica sol, and medium-particle silica sol, or both; and the solid mass percentage of the nano silica sol is 29% to 31%.

[0008] Furthermore, the raw materials include, by weight: 55 to 90 parts of deionized water, 9 to 20 parts of the nano-silica sol, 1 to 10 parts of a silane coupling agent, 0.001 to 1 part of a self-cleaning agent, 0.01 to 1 part of a surfactant, 0.01 to 1 part of a modified polyvinyl alcohol, 0.01 to 1 part of a water-based acrylic resin, 0.001 to 1 part of an antistatic agent, 1 to 5 parts of a curing agent, 1 to 5 parts of a leveling agent, and 0.1 to 1 part of an anti-wear agent; the self-cleaning agent includes nano-titanium dioxide; the nano-titanium dioxide includes anatase, and the particle size of the nano-titanium dioxide includes 2 to 10 nanometers.

[0009] Furthermore, in terms of weight ratio, the nano silica sol comprises: 4-10 parts of small-particle silica sol, 4-9 parts of medium-particle silica sol, and 1 part of large-particle silica sol; the particle size of the nano titanium dioxide is 2-3 nanometers.

[0010] Furthermore, in terms of weight ratio, the nano silica sol includes: 5 parts of small-particle silica sol, 5 parts of medium-particle silica sol, and 1 part of large-particle silica sol.

[0011] Furthermore, the silane coupling agent includes one or more of γ-aminopropyltriethoxysilane (KH-550), γ-glycidoxypropyltrimethoxysilane (KH-560), and γ-methacryloxypropyltrimethoxysilane (KH-570); the surfactant includes one or more of fatty alcohol polyoxyethylene ether, polyvinyl pyrrolidone, and hexadecyltrimethylammonium bromide; the modified polyvinyl alcohol includes resin-modified polyvinyl alcohol; the resin solid content of the water-based acrylic resin includes 42%; the antistatic agent includes one or more of nano-tin oxide, nano-zinc oxide, nano-antimony oxide, and nano-graphene; the curing agent includes one or more of lithium silicate, sodium silicate, and potassium silicate; the leveling agent includes one or more of ethylene glycol butyl ether, polyethylene glycol dimethyl ether, and ethanol; the wear-resistant agent includes nano-alumina or nano-zirconium oxide.

[0012] Furthermore, the solid of the nano-silica sol is silicon dioxide.

[0013] More preferably, the nano titanium dioxide is hydrophilic.

[0014] More preferably, the silane coupling agent is γ-aminopropyltriethoxysilane (KH-550).

[0015] More preferably, the surfactant is fatty alcohol polyoxyethylene ether.

[0016] More preferably, the antistatic agent is nano tin oxide.

[0017] Furthermore, the preparation method of the small-particle silica sol, the medium-particle silica sol or the large-particle silica sol includes: mixing tetraethyl orthosilicate as a silicon source with anhydrous ethanol, stirring and heating at the same time, slowly adding an ammonia diluent, and maintaining stirring and heating; in terms of weight, the usage ratio of tetraethyl orthosilicate, anhydrous ethanol and ammonia diluent includes 45 parts: 45 parts: 5 to 15 parts; and silica sols of different particle sizes are obtained by adjusting the usage of the ammonia diluent.

[0018] Furthermore, the mass ratio of water to ammonia in the ammonia dilution is 10:1; the heating temperature is 50°C, the stirring speed is 600-800 r / min, and the stirring and heating time is 12 hours; to obtain small-particle silica sol, the amount ratio of tetraethyl orthosilicate, anhydrous ethanol and ammonia dilution is 45 parts: 45 parts: 5 parts by weight; to obtain medium-particle silica sol, the amount ratio of tetraethyl orthosilicate, anhydrous ethanol and ammonia dilution is 45 parts: 45 parts: 10 parts by weight; to obtain large-particle silica sol, the amount ratio of tetraethyl orthosilicate, anhydrous ethanol and ammonia dilution is 45 parts: 45 parts: 15 parts by weight.

[0019] Accordingly, the present invention also provides a method for preparing the above-mentioned super-hydrophilic anti-reflective wear-resistant self-cleaning coating for photovoltaic glass cured at room temperature, comprising the following steps:

[0020] Step 1: Add the nano-silica sol into deionized water and stir for 10 minutes to make it evenly dispersed; then add a silane coupling agent and stir at room temperature for 2 hours to obtain solution A;

[0021] Step 2: Add nano titanium dioxide into deionized water and stir for 10 minutes to make it evenly dispersed to obtain solution B;

[0022] Step 3: Add the anti-wear agent into deionized water and stir for 10 minutes to make it evenly dispersed to obtain solution C;

[0023] Step 4: Add the solution B to the solution A under stirring, continue stirring for 10 minutes, add a surfactant, modified polyvinyl alcohol, water-based acrylic resin, an antistatic agent, a curing agent, and a leveling agent, then add the solution C, stir well for 1 hour, and age for 24 hours to obtain a solution D;

[0024] Step 5: Apply the solution D on the photovoltaic glass and dry it at room temperature to obtain the super-hydrophilic anti-reflective wear-resistant self-cleaning coating for photovoltaic glass that is cured at room temperature; the coating method includes any one of spin coating, dip coating, roller coating and spray coating.

[0025] Furthermore, the stirring speed after adding the silane coupling agent in step one is 800-1000r / min, the stirring speed in step four is 800-1000r / min, and the remaining stirring speeds in the preparation method are all 600-800r / min; step one, step two, step three, and step four are carried out at room temperature.

[0026] Without affecting the light transmittance, the nano-silicon dioxide with a smaller particle size of the present invention can fill the gaps between the nano-silicon dioxide with a larger particle size, and form a good bonding force between the coating particles and the substrate under the action of the curing agent and the resin. The present invention uses silica sols with different particle sizes for compounding to obtain a rougher surface than a coating with a single particle size, so that the surface hydroxyl hydrophilic groups per unit area of ​​the compounded coating are more; at the same time, the nano-silicon dioxide has a very large specific surface area, which provides more contact points for water molecules, increases the opportunity for interaction with water molecules, and thus makes the coating extremely hydrophilic.

[0027] Nano-silicon dioxide has a refractive index close to that of glass and is a commonly used anti-reflection material. However, when nano-silicon dioxide in solid form is directly added to water, it is easy to be unevenly dispersed, causing nanoparticles to agglomerate and the prepared coating to lose light transmittance. The present invention uses nano-silicon dioxide in the form of a sol, and the nanoparticles are evenly distributed in water. The coating prepared using the nano-silicon dioxide as the main film-forming agent has good light transmittance on the basis of strong hydrophilicity. The nano-silicon dioxide sol prepared by the present invention has an amount ratio of ethyl orthosilicate, anhydrous ethanol and ammonia diluent in the raw materials of 45 parts: 45 parts: (5-15) parts by weight. The amount of ammonia in the raw materials affects the hydrolysis reaction rate of ethyl orthosilicate. A moderate amount can obtain silicon dioxide with a small particle size, while an excessive amount will accelerate the reaction. The silicate radicals generated by hydrolysis will aggregate to form large particles of silicon dioxide after polycondensation.

[0028] The self-cleaning agent of the present invention uses anatase titanium dioxide, which has higher light transmittance than other crystal forms. At the same time, hydrophilic nano titanium dioxide can be dissolved and dispersed in water. The nano particles can fully exert their photocatalytic effect when they are evenly dispersed in water, thereby improving the self-cleaning and anti-fouling effect of the coating. Among them, nano titanium dioxide with a small particle size (2-3nm) has weaker scattering ability, allowing light to pass more easily.

[0029] Other raw materials of the coating of the present invention also play a role in synergistically enhancing the performance of the coating: under alkaline conditions, the silane coupling agent is hydrolyzed to fill the gaps between the nano silicon dioxide particles, making the coating more compact and hard; the functional groups in the surfactant can increase the hydrophilicity of the coating, reduce the surface tension of the solution, and more easily wet the surface of the material during coating, making the coating more uniform; the modified polyvinyl alcohol contains a large amount of hydroxyl groups, which can be grafted with the nano silicon dioxide to improve the mechanical properties of the coating; the water-based acrylic resin has good weather resistance, can resist the erosion of ultraviolet rays and high humidity, improves the aging resistance of the coating, and interacts with the silane coupling agent to improve the water resistance of the coating; the antistatic agent nano tin oxide has high light transmittance and conductivity, increases its conductivity without affecting the light transmittance of the coating, reduces the electrostatic adsorption of dust, and plays an anti-fouling effect.

[0030] Compared with the prior art, the implementation of the present invention has the following beneficial effects:

[0031] 1. Nano-silicon dioxide has a very large specific surface area, providing more contact points for water molecules. Therefore, the super-hydrophilic anti-reflective wear-resistant self-cleaning coating of the present invention has super-hydrophilicity, and the water contact angle is below 10°; the coating of the present invention also significantly improves the hydrophilicity, antistatic property, anti-reflective property, wear resistance and other properties of glass.

[0032] 2. Without affecting the light transmittance, the present invention uses three silica sols with different silica particle sizes for compounding to obtain a rougher surface than a coating with a single particle size, with more surface hydroxyl hydrophilic groups, so that the coating of the present invention has stronger hydrophilicity and a water contact angle of less than 8°.

[0033] 3. The present invention uses nano-silicon dioxide in the form of sol, preferably anatase nano-titanium dioxide in a certain particle size range, and other raw materials to prepare a self-cleaning coating in coordination, so that the coating has excellent light transmittance.

[0034] 4. The super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating of the present invention can not only significantly enhance the self-cleaning effect and light transmission performance of glass, but also improve the photoelectric conversion efficiency in photovoltaic power generation when applied to photovoltaic module glass.

[0035] 5. The coating of the present invention is a non-solvent antireflection film, which is environmentally friendly and can be cured at room temperature. The required process and equipment are simple, and therefore it is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a contact angle test diagram of the coating of Example 9 of the present invention;

[0037] Figure 2The transmittance test comparison of the glass of the embodiment of the present invention and the blank group glass (the curves from top to bottom at a wavelength of 380nm are the test data of embodiment 9, embodiment 10, embodiment 11, embodiment 12, embodiment 13, and the blank group glass);

[0038] Figure 3 This is a comparison of the actual power generation application of the glass of Example 9 of the present invention and the glass without coating;

[0039] Figure 4 The self-cleaning effect of the glass of Example 9 of the present invention and the blank group of glass are compared. DETAILED DESCRIPTION

[0040] To make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with specific examples and drawings. Unless otherwise specified, the reagents and materials used in the following examples and comparative examples are conventional commercial products.

[0041] Preparation Example (Silica Sol of Various Particle Sizes)

[0042] Preparation of small-particle silica sol: The mass ratio of water to ammonia in the ammonia diluent is 10:1. By weight, the usage ratio of ethyl orthosilicate, anhydrous ethanol and ammonia diluent is 45 parts: 45 parts: 5 parts. Ethyl orthosilicate is used as a silicon source and mixed with anhydrous ethanol, stirred and heated at the same time, and the ammonia diluent is slowly added dropwise; the heating temperature is 50°C, the stirring speed is 600-800r / min, and the stirring and heating are maintained for 12 hours to obtain a silica sol with a silica particle size of 15-20 nanometers.

[0043] Preparation of medium-sized silica sol: The mass ratio of water to ammonia in the ammonia diluent is 10:1. By weight, the usage ratio of ethyl orthosilicate, anhydrous ethanol and ammonia diluent is 45 parts: 45 parts: 10 parts. Ethyl orthosilicate is used as a silicon source and mixed with anhydrous ethanol, stirred and heated at the same time, and the ammonia diluent is slowly added dropwise; the heating temperature is 50°C, the stirring speed is 600-800r / min, and the stirring and heating are maintained for 12 hours to obtain a silica sol with a silica particle size of 30-40 nanometers.

[0044] Preparation of large-particle silica sol: The mass ratio of water to ammonia in the ammonia diluent is 10:1. By weight, the usage ratio of ethyl orthosilicate, anhydrous ethanol and ammonia diluent is 45 parts: 45 parts: 15 parts. Ethyl orthosilicate is used as a silicon source and mixed with anhydrous ethanol, stirred and heated at the same time, and the ammonia diluent is slowly added dropwise; the heating temperature is 50°C, the stirring speed is 600-800r / min, and the stirring and heating are maintained for 12 hours to obtain a silica sol with a silica particle size of 50-60 nanometers.

[0045] Example 1

[0046] Step 1: Raw materials are weighed in parts by weight, 50 parts of deionized water and 10 parts of silica sol with a silica particle size of 15 to 20 nanometers in the preparation example are weighed, stirred for 10 minutes to disperse evenly at a speed of 600 to 800 r / min, 1 part of silane coupling agent KH-550 is added, the speed is increased to 800 to 1000 r / min, and stirred at room temperature for 2 hours to obtain solution A.

[0047] Step 2: Add 0.001 parts of 2-3 nanometer titanium dioxide into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution B.

[0048] Step 3: Add 0.1 parts of anti-wear agent nano-alumina into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution C.

[0049] Step 4: Add solution B to solution A while stirring, continue stirring for 10 minutes, the solution is light blue, add 0.05 parts of surfactant fatty alcohol polyoxyethylene ether, add 0.5 parts of modified polyvinyl alcohol, add 0.5 parts of water-based acrylic resin, add 0.002 parts of nano-tin oxide, add 3 parts of lithium silicate, add 3 parts of ethylene glycol butyl ether and then add solution C, stir thoroughly for 1 hour at a speed of 800-1000r / min, age for 24 hours to obtain solution D.

[0050] Step 5: Apply solution D to the photovoltaic glass by spin coating, dip coating, roller coating or spray coating, and dry it at room temperature for 10 minutes to obtain a super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass.

[0051] Example 2

[0052] Step 1: Raw materials are weighed in parts by weight, 50 parts of deionized water and 10 parts of silica sol with a silica particle size of 30 to 40 nanometers in the preparation example are weighed, stirred for 10 minutes to disperse evenly at a speed of 600 to 800 r / min, 1 part of silane coupling agent KH-550 is added, the speed is increased to 800 to 1000 r / min, and stirred at room temperature for 2 hours to obtain solution A.

[0053] Step 2: Add 0.001 parts of 2-3 nanometer titanium dioxide into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution B.

[0054] Step 3: Add 0.1 parts of anti-wear agent nano-alumina into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution C.

[0055] Step 4: Add solution B to solution A while stirring, continue stirring for 10 minutes, the solution is light blue, add 0.05 parts of surfactant fatty alcohol polyoxyethylene ether, add 0.5 parts of modified polyvinyl alcohol, add 0.5 parts of water-based acrylic resin, add 0.002 parts of nano-tin oxide, add 3 parts of lithium silicate, add 3 parts of ethylene glycol butyl ether and then add solution C, stir thoroughly for 1 hour at a speed of 800-1000r / min, age for 24 hours to obtain solution D.

[0056] Step 5: Apply solution D to the photovoltaic glass by spin coating, dip coating, roller coating or spray coating, and dry it at room temperature for 10 minutes to obtain a super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass.

[0057] Example 3

[0058] Step 1: Raw materials are weighed in parts by weight, 50 parts of deionized water and 10 parts of silica sol with a silica particle size of 50 to 60 nanometers in the preparation example are weighed, stirred for 10 minutes to disperse evenly at a speed of 600 to 800 r / min, 1 part of silane coupling agent KH-550 is added, the speed is increased to 800 to 1000 r / min, and stirred at room temperature for 2 hours to obtain solution A.

[0059] Step 2: Add 0.001 parts of 2-3 nanometer titanium dioxide into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution B.

[0060] Step 3: Add 0.1 parts of anti-wear agent nano-alumina into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution C.

[0061] Step 4: Add solution B to solution A while stirring, continue stirring for 10 minutes, the solution is light blue, add 0.05 parts of surfactant fatty alcohol polyoxyethylene ether, add 0.5 parts of modified polyvinyl alcohol, add 0.5 parts of water-based acrylic resin, add 0.002 parts of nano-tin oxide, add 3 parts of lithium silicate, add 3 parts of ethylene glycol butyl ether and then add solution C, stir thoroughly for 1 hour at a speed of 800-1000r / min, age for 24 hours to obtain solution D.

[0062] Step 5: Apply solution D to the photovoltaic glass by spin coating, dip coating, roller coating or spray coating, and dry it at room temperature for 10 minutes to obtain a super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass.

[0063] Example 4

[0064] Step 1: Raw materials are weighed by weight, 50 parts of deionized water, 5 parts of silica sol with a silica particle size of 15 to 20 nanometers in the preparation example, and 5 parts of silica sol with a particle size of 30 to 40 nanometers, and stirred for 10 minutes to disperse evenly at a speed of 600 to 800 r / min, 1 part of silane coupling agent KH-550 is added, the speed is increased to 800 to 1000 r / min, and stirred at room temperature for 2 hours to obtain solution A.

[0065] Step 2: Add 0.001 parts of 2-3 nanometer titanium dioxide into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution B.

[0066] Step 3: Add 0.1 parts of anti-wear agent nano-alumina into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution C.

[0067] Step 4: Add solution B to solution A while stirring, continue stirring for 10 minutes, the solution is light blue, add 0.05 parts of surfactant fatty alcohol polyoxyethylene ether, add 0.5 parts of modified polyvinyl alcohol, add 0.5 parts of water-based acrylic resin, add 0.002 parts of nano-tin oxide, add 3 parts of lithium silicate, add 3 parts of ethylene glycol butyl ether and then add solution C, stir thoroughly for 1 hour at a speed of 800-1000r / min, age for 24 hours to obtain solution D.

[0068] Step 5: Apply solution D to the photovoltaic glass by spin coating, dip coating, roller coating or spray coating, and dry it at room temperature for 10 minutes to obtain a super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass.

[0069] Example 5

[0070] Step 1: Raw materials are weighed by weight, 50 parts of deionized water, 5 parts of silica sol with a silica particle size of 30 to 40 nanometers in the preparation example, and 5 parts of silica sol with a particle size of 50 to 60 nanometers. Stir for 10 minutes to disperse evenly at a speed of 600 to 800 r / min, add 1 part of silane coupling agent KH-550, increase the speed to 800 to 1000 r / min, and stir at room temperature for 2 hours to obtain solution A.

[0071] Step 2: Add 0.001 parts of 2-3 nanometer titanium dioxide into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution B.

[0072] Step 3: Add 0.1 parts of anti-wear agent nano-alumina into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution C.

[0073] Step 4: Add solution B to solution A while stirring, continue stirring for 10 minutes, the solution is light blue, add 0.05 parts of surfactant fatty alcohol polyoxyethylene ether, add 0.5 parts of modified polyvinyl alcohol, add 0.5 parts of water-based acrylic resin, add 0.002 parts of nano-tin oxide, add 3 parts of lithium silicate, add 3 parts of ethylene glycol butyl ether and then add solution C, stir thoroughly for 1 hour at a speed of 800-1000r / min, age for 24 hours to obtain solution D.

[0074] Step 5: Apply solution D to the photovoltaic glass by spin coating, dip coating, roller coating or spray coating, and dry it at room temperature for 10 minutes to obtain a super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass.

[0075] Example 6

[0076] Step 1: Raw materials are weighed by weight, 50 parts of deionized water, 5 parts of silica sol with a silica particle size of 15 to 20 nanometers in the preparation example, and 5 parts of silica sol with a particle size of 50 to 60 nanometers. Stir for 10 minutes to disperse evenly at a speed of 600 to 800 r / min, add 1 part of silane coupling agent KH-550, increase the speed to 800 to 1000 r / min, and stir at room temperature for 2 hours to obtain solution A.

[0077] Step 2: Add 0.001 parts of 2-3 nanometer titanium dioxide into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution B.

[0078] Step 3: Add 0.1 parts of anti-wear agent nano-alumina into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution C.

[0079] Step 4: Add solution B to solution A while stirring, continue stirring for 10 minutes, the solution is light blue, add 0.05 parts of surfactant fatty alcohol polyoxyethylene ether, add 0.5 parts of modified polyvinyl alcohol, add 0.5 parts of water-based acrylic resin, add 0.002 parts of nano-tin oxide, add 3 parts of lithium silicate, add 3 parts of ethylene glycol butyl ether and then add solution C, stir thoroughly for 1 hour at a speed of 800-1000r / min, age for 24 hours to obtain solution D.

[0080] Step 5: Apply solution D to the photovoltaic glass by spin coating, dip coating, roller coating or spray coating, and dry it at room temperature for 10 minutes to obtain a super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass.

[0081] Example 7

[0082] Step 1: Raw materials are weighed by weight, 50 parts of deionized water, 5 parts of silica sol with a silica particle size of 15 to 20 nanometers in the preparation example, 5 parts of silica sol with a particle size of 30 to 40 nanometers, and 1 part of silica sol with a particle size of 50 to 60 nanometers, and stirred for 10 minutes to disperse evenly at a speed of 600 to 800 r / min, 1 part of silane coupling agent KH-550 is added, the speed is increased to 800 to 1000 r / min, and stirred at room temperature for 2 hours to obtain solution A.

[0083] Step 2: Add 0.001 parts of 10 nanometer titanium dioxide into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution B.

[0084] Step 3: Add 0.1 parts of anti-wear agent nano-alumina into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution C.

[0085] Step 4: Add solution B to solution A while stirring, continue stirring for 10 minutes, the solution is light blue, add 0.05 parts of surfactant fatty alcohol polyoxyethylene ether, add 0.5 parts of modified polyvinyl alcohol, add 0.5 parts of water-based acrylic resin, add 0.002 parts of nano-tin oxide, add 3 parts of lithium silicate, add 3 parts of ethylene glycol butyl ether and then add solution C, stir thoroughly for 1 hour at a speed of 800-1000r / min, age for 24 hours to obtain solution D.

[0086] Step 5: Apply solution D to the photovoltaic glass by spin coating, dip coating, roller coating or spray coating, and dry it at room temperature for 10 minutes to obtain a super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass.

[0087] Example 8

[0088] Step 1: Raw materials are weighed by weight, 50 parts of deionized water, 5 parts of silica sol with a silica particle size of 15 to 20 nanometers in the preparation example, 5 parts of silica sol with a particle size of 30 to 40 nanometers, and 1 part of silica sol with a particle size of 50 to 60 nanometers, and stirred for 10 minutes to disperse evenly at a speed of 600 to 800 r / min, 1 part of silane coupling agent KH-550 is added, the speed is increased to 800 to 1000 r / min, and stirred at room temperature for 2 hours to obtain solution A.

[0089] Step 2: Add 0.001 parts of 5 nanometer titanium dioxide into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution B.

[0090] Step 3: Add 0.1 parts of anti-wear agent nano-alumina into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution C.

[0091] Step 4: Add solution B to solution A while stirring, continue stirring for 10 minutes, the solution is light blue, add 0.05 parts of surfactant fatty alcohol polyoxyethylene ether, add 0.5 parts of modified polyvinyl alcohol, add 0.5 parts of water-based acrylic resin, add 0.002 parts of nano-tin oxide, add 3 parts of lithium silicate, add 3 parts of ethylene glycol butyl ether and then add solution C, stir thoroughly for 1 hour at a speed of 800-1000r / min, age for 24 hours to obtain solution D.

[0092] Step 5: Apply solution D to the photovoltaic glass by spin coating, dip coating, roller coating or spray coating, and dry it at room temperature for 10 minutes to obtain a super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass.

[0093] Example 9

[0094] Step 1: Raw materials are weighed by weight, 50 parts of deionized water, 5 parts of silica sol with a silica particle size of 15 to 20 nanometers in the preparation example, 5 parts of silica sol with a particle size of 30 to 40 nanometers, and 1 part of silica sol with a particle size of 50 to 60 nanometers, and stirred for 10 minutes to disperse evenly at a speed of 600 to 800 r / min, 1 part of silane coupling agent KH-550 is added, the speed is increased to 800 to 1000 r / min, and stirred at room temperature for 2 hours to obtain solution A.

[0095] Step 2: Add 0.001 parts of 2-3 nanometer titanium dioxide into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution B.

[0096] Step 3: Add 0.1 parts of anti-wear agent nano-alumina into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution C.

[0097] Step 4: Add solution B to solution A while stirring, continue stirring for 10 minutes, the solution is light blue, add 0.05 parts of surfactant fatty alcohol polyoxyethylene ether, add 0.5 parts of modified polyvinyl alcohol, add 0.5 parts of water-based acrylic resin, add 0.002 parts of nano-tin oxide, add 3 parts of lithium silicate, add 3 parts of ethylene glycol butyl ether and then add solution C, stir thoroughly for 1 hour at a speed of 800-1000r / min, age for 24 hours to obtain solution D.

[0098] Step 5: Apply solution D to the photovoltaic glass by spin coating, dip coating, roller coating or spray coating, and dry it at room temperature for 10 minutes to obtain a super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass.

[0099] Example 10

[0100] Step 1: Raw materials are weighed by weight, 50 parts of deionized water, 4 parts of silica sol with a silica particle size of 15 to 20 nanometers in the preparation example, 4 parts of silica sol with a particle size of 30 to 40 nanometers, and 1 part of silica sol with a particle size of 50 to 60 nanometers, and stirred for 10 minutes to disperse evenly at a speed of 600 to 800 r / min, 2 parts of silane coupling agent KH-550 are added, the speed is increased to 800 to 1000 r / min, and stirred at room temperature for 2 hours to obtain solution A.

[0101] Step 2: Add 0.001 parts of 2-3 nanometer titanium dioxide into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution B.

[0102] Step 3: Add 0.1 parts of anti-wear agent nano-alumina into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution C.

[0103] Step 4: Add solution B to solution A while stirring, continue stirring for 10 minutes, the solution is light blue, add 0.05 parts of surfactant fatty alcohol polyoxyethylene ether, add 0.5 parts of modified polyvinyl alcohol, add 0.5 parts of water-based acrylic resin, add 0.002 parts of nano-tin oxide, add 3 parts of lithium silicate, add 3 parts of ethylene glycol butyl ether and then add solution C, stir thoroughly for 1 hour at a speed of 800-1000r / min, age for 24 hours to obtain solution D.

[0104] Step 5: Apply solution D to the photovoltaic glass by spin coating, dip coating, roller coating or spray coating, and dry it at room temperature for 10 minutes to obtain a super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass.

[0105] Embodiment 11

[0106] Step 1: Raw materials are weighed by weight, 50 parts of deionized water, 6 parts of silica sol with a silica particle size of 15 to 20 nanometers in the preparation example, 6 parts of silica sol with a particle size of 30 to 40 nanometers, and 1 part of silica sol with a particle size of 50 to 60 nanometers. Stir for 10 minutes to disperse evenly at a speed of 600 to 800 r / min, add 1 part of silane coupling agent KH-550, increase the speed to 800 to 1000 r / min, and stir at room temperature for 2 hours to obtain solution A.

[0107] Step 2: Add 0.5 parts of 2-3 nanometer titanium dioxide into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution B.

[0108] Step 3: Add 0.2 parts of anti-wear agent nano-alumina into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution C.

[0109] Step 4: Add solution B to solution A while stirring, continue stirring for 10 minutes, the solution is light blue, add 0.1 parts of surfactant fatty alcohol polyoxyethylene ether, add 0.1 parts of modified polyvinyl alcohol, add 0.5 parts of water-based acrylic resin, add 0.002 parts of nano-tin oxide, add 3 parts of lithium silicate, add 3 parts of ethylene glycol butyl ether and then add solution C, stir well for 1 hour at a speed of 800-1000r / min, age for 24 hours to obtain solution D.

[0110] Step 5: Apply solution D to the photovoltaic glass by spin coating, dip coating, roller coating or spray coating, and dry it at room temperature for 10 minutes to obtain a super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass.

[0111] Example 12

[0112] Step 1: Raw materials are weighed by weight, 50 parts of deionized water, 8 parts of silica sol with a silica particle size of 15 to 20 nanometers in the preparation example, 8 parts of silica sol with a particle size of 30 to 40 nanometers, and 1 part of silica sol with a particle size of 50 to 60 nanometers. Stir for 10 minutes to disperse evenly at a speed of 600 to 800 r / min, add 3 parts of silane coupling agent KH-550, increase the speed to 800 to 1000 r / min, and stir at room temperature for 2 hours to obtain solution A.

[0113] Step 2: Add 0.5 parts of 2-3 nanometer titanium dioxide into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution B.

[0114] Step 3: Add 0.3 parts of anti-wear agent nano-alumina into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution C.

[0115] Step 4: Add solution B to solution A while stirring, continue stirring for 10 minutes, the solution is light blue, add 1 part of surfactant fatty alcohol polyoxyethylene ether, add 0.5 parts of modified polyvinyl alcohol, add 0.5 parts of water-based acrylic resin, add 0.01 parts of nano-tin oxide, add 5 parts of lithium silicate, add 5 parts of ethylene glycol butyl ether and then add solution C, stir thoroughly for 1 hour at a speed of 800-1000r / min, age for 24 hours to obtain solution D.

[0116] Step 5: Apply solution D to the photovoltaic glass by spin coating, dip coating, roller coating or spray coating, and dry it at room temperature for 10 minutes to obtain a super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass.

[0117] Embodiment 13

[0118] Step 1: Raw materials are weighed by weight, 50 parts of deionized water, 10 parts of silica sol with a silica particle size of 15 to 20 nanometers in the preparation example, 9 parts of silica sol with a particle size of 30 to 40 nanometers, and 1 part of silica sol with a particle size of 50 to 60 nanometers. Stir for 10 minutes to disperse evenly at a speed of 600 to 800 r / min, add 10 parts of silane coupling agent KH-550, increase the speed to 800 to 1000 r / min, and stir at room temperature for 2 hours to obtain solution A.

[0119] Step 2: Add 0.1 parts of 2-3 nanometer titanium dioxide into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution B.

[0120] Step 3: Add 0.2 parts of anti-wear agent nano-alumina into 18 parts of deionized water, stir for 10 minutes to disperse evenly at a speed of 600-800 r / min to obtain solution C.

[0121] Step 4: Add solution B to solution A while stirring, continue stirring for 10 minutes, the solution is light blue, add 1 part of surfactant fatty alcohol polyoxyethylene ether, add 0.5 parts of modified polyvinyl alcohol, add 0.5 parts of water-based acrylic resin, add 0.1 parts of nano-tin oxide, add 3 parts of lithium silicate, add 5 parts of ethylene glycol butyl ether and then add solution C, stir thoroughly for 1 hour at a speed of 800-1000r / min, age for 24 hours to obtain solution D.

[0122] Step 5: Apply solution D to the photovoltaic glass by spin coating, dip coating, roller coating or spray coating, and dry it at room temperature for 10 minutes to obtain a super-hydrophilic, anti-reflective, wear-resistant and self-cleaning coating for photovoltaic glass.

[0123] Performance Testing

[0124] The performance tests were conducted on the glass samples coated with the coatings prepared in Examples 1 to 13, and the glass samples without coatings were used as blank group samples. The specific test methods and results are as follows.

[0125] Surface antistatic performance: The surface resistance of the sample to be tested was tested using a MEGOHMMETER. The smaller the resistance, the better the antistatic performance. Before testing, ensure that the surface of the sample to be tested is dry and clean. The results are compared in Table 1. The resistance of each embodiment is significantly lower than that of the blank group. It can be seen that the present invention uses nano-tin oxide as an antistatic agent to make the coating have excellent antistatic performance. Therefore, dust is difficult to adhere to the glass surface and has anti-fouling properties. The amount of antistatic agent used in Example 13 is much higher than that in other embodiments. Therefore, the surface resistance of the coating in Example 13 reaches 1.32x10 7 Ω, which means that the surface antistatic performance is the best in the embodiment of the present invention, and the anti-fouling and self-cleaning properties are excellent.

[0126] Pencil hardness: Use a pencil hardness tester to measure the pencil hardness of the test sample, and test the hardness of the coating from low (6B) to high (6H) according to the hardness of the pencil. After the pencil hardness tester has finished scratching the sample, use a 3D laser microscope at 5X magnification to observe whether the coating is damaged. If the coating is damaged, it means that the hardness of the coating is lower than the hardness of the pencil. Record and use the highest hardness of the pencil that does not damage the coating as the coating hardness of the sample. See Table 1 for the hardness test results. It can be seen that the hardness of the embodiment coating is between 2-3H, and all have certain wear resistance and durability. Among them, the hardness of embodiment 12 is the best among the embodiments of the present invention.

[0127] Contact angle: Use a contact angle meter to test the water drop contact angle of the test sample. The volume of the water droplet dropped each time is 5μL. Test the water drop contact angle of at least 3 positions of each test sample, and record and calculate the average value as the water drop contact angle value of the sample. Ensure that the surface of the test sample is dry and clean before testing.

[0128] The contact angle results are compared in Table 1, where the contact angles of Examples 1 to 3 are greater than or close to 10°, indicating that the coatings using a single silica particle size do not reach the level of super-hydrophilicity; further, in Examples 4 to 6 using two particle sizes, the contact angle of Example 4, which does not use silica with a particle size of 50 to 60 nanometers, is still greater than 10°, while the contact angles of Examples 5 to 6 are less than 10°, indicating that the coatings prepared by compounding silica with a particle size of 50 to 60 nanometers and silica with a particle size of 15 to 20 nanometers or 30 to 40 nanometers in the formulation of the present invention have super-hydrophilicity. Further research on the synergistic compounding of the three particle sizes revealed that the contact angles of the coatings of Examples 7 to 13 were all less than 8°, and the super-hydrophilicity of the coatings was better than that of the coatings compounded with only two silica particle sizes; among them, the contact angle test results of Example 9 are shown in Table 1. Figure 1 , the contact angle is 6.96°.

[0129] Transmittance: Use UV-visible spectrophotometer to test the transmittance of the sample in the wavelength range of 380-750nm. Before testing, ensure that the surface of the sample is dry and clean. Figure 2 The transmittance in Table 1 is the average value calculated based on the transmittance of each 1 nm wavelength in the measurement section. Figure 2 The transmittance of the examples in Table 1 is higher than that of the blank group, which shows that the coatings of the examples have higher permeability. In the examples of three kinds of silica particle size compounding, although the nano silica sols used in Examples 7 to 9 are exactly the same, the transmittance of Examples 7 and 8 is significantly lower than that of Example 9, and the main difference lies in the particle size of titanium dioxide. Therefore, the transmittance of Examples 9 to 13 using nano titanium dioxide with a particle size of 2 to 3 nm is better.

[0130] Table 1 Performance test data of Examples 1 to 13 and blank group

[0131]

[0132]

[0133] In summary, the coatings of the present invention (Examples 1 to 13) are all wear-resistant and durable; the surface is composed of 10 11 The Ω level is reduced to 10 with coating 7 Ω level, indicating that the antistatic property of the photovoltaic glass coated with the coating of the present invention (Examples 1 to 13) is greatly improved; further taking transmittance and contact angle as key properties, the coatings (Examples 5 to 13) prepared by compounding silica with a particle size of 50 to 60 nanometers and silica with a particle size of 15 to 20 nanometers or 30 to 40 nanometers in the formula of the present invention have contact angles of less than 10°, and have super hydrophilicity; and the coatings (Examples 9 to 13) of nano-silica sol in which nano-titanium dioxide has a particle size of 2 to 3 nm and a compound of silica with a particle size of 15 to 20 nanometers, 30 to 40 nanometers and 50 to 60 nanometers have better light transmittance.

[0134] Based on the performance test data of Examples 9 to 13, considering the effect of increasing power generation on the photovoltaic power generation group, when other performance differences are not large, the group with the highest transmittance (Example 9) is selected as the preferred group.

[0135] Application Effect

[0136] The solution obtained in Example 9 was coated on the surface of the photovoltaic module glass as a coated group, and the photovoltaic module glass without coating after cleaning was used as an uncoated group. These two groups of glass were used for photovoltaic power generation testing. Specifically, both groups used the same type of photovoltaic power generation modules with a module capacity of 130Kw. The power generation data was continuously collected for 27 days through the inverter. The collected power generation data is shown in Figure 3 .Depend on Figure 3 It can be seen that compared with the group without coating, the power generation of the group with the coating of the present invention is improved, and the average power generation is increased by about 3%. The super-hydrophilic anti-reflective wear-resistant self-cleaning coating of the present invention can not only enhance the hydrophilicity, antistatic property, anti-reflective property and other properties of photovoltaic glass, but also has a certain effect on improving the actual photoelectric conversion efficiency.

[0137] Ultra-white glass was selected as photovoltaic glass, and the solution obtained in Example 9 was coated on the surface of the photovoltaic glass. The photovoltaic glass without coating was used as a blank group. After cleaning, the two groups of glass were tested for self-cleaning effects, as follows: 15g of naturally collected dust was weighed in the same beaker, the glass was placed at an angle of 70° to the horizontal plane, and the dust was poured on the top of the glass near the edge to observe the residual situation of the fallen dust. The test results are compared in Figure 4 It can be seen that the blank group has obvious dust, while Example 9 has almost no dust. Therefore, the super-hydrophilic anti-reflective, wear-resistant and self-cleaning coating of the present invention significantly enhances the anti-fouling and self-cleaning effects of photovoltaic glass.

[0138] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A super-hydrophilic anti-reflective wear-resistant self-cleaning coating for photovoltaic glass cured at room temperature, characterized in that: The film is solidified with nano-silica sol as the main film-forming agent; the nano-silica sol includes a plurality of small-particle silica sol, medium-particle silica sol and large-particle silica sol; the silica particle size of the small-particle silica sol includes 15 to 20 nanometers, the silica particle size of the medium-particle silica sol includes 30 to 40 nanometers, and the silica particle size of the large-particle silica sol includes 50 to 60 nanometers.

2. The super-hydrophilic anti-reflective wear-resistant self-cleaning coating for photovoltaic glass curing at room temperature according to claim 1, characterized in that: The raw materials include a self-cleaning agent; the nano silica sol is a mixture of the large-particle silica sol, the small-particle silica sol, and the medium-particle silica sol; and the solid mass percentage of the nano silica sol is 29% to 31%.

3. The super-hydrophilic anti-reflective wear-resistant self-cleaning coating for photovoltaic glass curing at room temperature according to claim 1, characterized in that: The raw materials include, by weight: 55-90 parts of deionized water, 9-20 parts of the nano-silica sol, 1-10 parts of silane coupling agent, 0.001-1 part of self-cleaning agent, 0.01-1 part of surfactant, 0.01-1 part of modified polyvinyl alcohol, 0.01-1 part of water-based acrylic resin, 0.001-1 part of antistatic agent, 1-5 parts of curing agent, 1-5 parts of leveling agent, and 0.1-1 part of wear-resistant agent; the self-cleaning agent includes nano-titanium dioxide; the nano-titanium dioxide includes anatase type, and the particle size of the nano-titanium dioxide includes 2-10 nanometers.

4. The super-hydrophilic anti-reflective wear-resistant self-cleaning coating for photovoltaic glass curing at room temperature according to claim 3, characterized in that: In terms of weight ratio, the nano silica sol comprises: 4 to 10 parts of the small-particle silica sol, 4 to 9 parts of the medium-particle silica sol, and 1 part of the large-particle silica sol; the particle size of the nano titanium dioxide is 2 to 3 nanometers.

5. The super-hydrophilic anti-reflective wear-resistant self-cleaning coating for photovoltaic glass curing at room temperature according to claim 4, characterized in that: In terms of weight ratio, the nano silica sol comprises: 5 parts of the small-particle silica sol, 5 parts of the medium-particle silica sol, and 1 part of the large-particle silica sol.

6. The super-hydrophilic anti-reflective wear-resistant self-cleaning coating for photovoltaic glass curing at room temperature according to claim 3, characterized in that: The silane coupling agent includes one or more of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane; the surfactant includes one or more of fatty alcohol polyoxyethylene ether, polyvinyl pyrrolidone, and hexadecyltrimethylammonium bromide; the modified polyvinyl alcohol includes resin-modified polyvinyl alcohol; the resin solid content of the water-based acrylic resin includes 42%; the antistatic agent includes one or more of nano-tin oxide, nano-zinc oxide, nano-antimony oxide, and nano-graphene; the curing agent includes one or more of lithium silicate, sodium silicate, and potassium silicate; the leveling agent includes one or more of ethylene glycol butyl ether, polyethylene glycol dimethyl ether, and ethanol; the wear-resistant agent includes nano-alumina or nano-zirconium oxide.

7. The super-hydrophilic anti-reflective wear-resistant self-cleaning coating for photovoltaic glass curing at room temperature according to any one of claims 1 to 6, characterized in that: The preparation method of the small-particle silica sol, the medium-particle silica sol or the large-particle silica sol comprises: taking tetraethyl orthosilicate as a silicon source and mixing it with anhydrous ethanol, stirring and heating at the same time, slowly dropping an ammonia diluent, and maintaining stirring and heating to obtain the silica sol; in terms of weight, the usage ratio of tetraethyl orthosilicate, anhydrous ethanol and ammonia diluent comprises 45 parts: 45 parts: 5 to 15 parts; and silica sols with different particle sizes are obtained by adjusting the usage of the ammonia diluent.

8. The super-hydrophilic anti-reflective wear-resistant self-cleaning coating for photovoltaic glass curing at room temperature according to claim 7, characterized in that: The mass ratio of water to ammonia in the ammonia diluent is 10:1; the heating temperature is 50°C, the stirring speed is 600-800 r / min, and the stirring and heating time is 12 hours; to obtain the small-particle silica sol, the amount ratio of ethyl orthosilicate, anhydrous ethanol and ammonia diluent is 45 parts: 45 parts: 5 parts by weight; to obtain the medium-particle silica sol, the amount ratio of ethyl orthosilicate, anhydrous ethanol and ammonia diluent is 45 parts: 45 parts: 10 parts by weight; To obtain the large-particle silica sol, the usage ratio of ethyl orthosilicate, anhydrous ethanol and ammonia diluent is 45 parts:45 parts:15 parts by weight.

9. A method for preparing a super-hydrophilic anti-reflective wear-resistant self-cleaning coating for photovoltaic glass cured at room temperature as claimed in claim 1, characterized in that: The steps include: Step 1: Add the nano-silica sol into deionized water and stir for 10 minutes to make it evenly dispersed; then add a silane coupling agent and stir at room temperature for 2 hours to obtain solution A; Step 2: Add nano titanium dioxide into deionized water and stir for 10 minutes to make it evenly dispersed to obtain solution B; Step 3: Add the anti-wear agent into deionized water and stir for 10 minutes to make it evenly dispersed to obtain solution C; Step 4: Add the solution B to the solution A under stirring, continue stirring for 10 minutes, add a surfactant, modified polyvinyl alcohol, water-based acrylic resin, an antistatic agent, a curing agent, and a leveling agent, then add the solution C, stir well for 1 hour, and age for 24 hours to obtain a solution D; Step 5: Apply the solution D on the photovoltaic glass and dry it at room temperature to obtain the super-hydrophilic anti-reflective wear-resistant self-cleaning coating for photovoltaic glass that is cured at room temperature; the coating method includes any one of spin coating, dip coating, roller coating and spray coating.

10. The method for preparing a super-hydrophilic anti-reflective wear-resistant self-cleaning coating for photovoltaic glass cured at room temperature according to claim 9, characterized in that: After adding the silane coupling agent in step one, the stirring speed is 800-1000r / min, the stirring speed in step four is 800-1000r / min, and the remaining stirring speeds in the preparation method are all 600-800r / min; step one, step two, step three, and step four are carried out at room temperature.

Citation Information

Patent Citations

  • Coating composition and preparation method thereof, and self-cleaning nano coating and preparation method thereof

    CN112694769A

  • Anti-reflection liquid for photovoltaic module glass as well as preparation method and application of anti-reflection liquid

    CN113755041A

  • Photovoltaic glass self-cleaning dustproof anti-reflection nanometer material and preparation method thereof

    CN116891645A

  • Self-cleaning coating for ceramic-based photovoltaic glass and preparation method of self-cleaning coating

    CN118222122A

Cited By

  • Protective nano hard coating and preparation method thereof

    CN119978864A

  • A protective nano hard coating and its preparation method

    CN119978864B

  • Mesoporous silica microsphere solution and anti-reflection composite coating liquid

    CN120903512A

  • Long-service-life antifouling coating for panel for photovoltaic module and preparation method of long-service-life antifouling coating

    CN121086653A

  • A panel for photovoltaic modules using a long-life anti-soiling coating and a method for its production

    CN121086653B